Phylogenetic relationships of Malesian Lady Ferns (Athyrium) provide insight into long-standing species complexes - Wardani, Wita; Salamah, Andi; Adjie, Bayu; Yulita, Kusumadewi Sri; Fraser-Jenkins, Christopher Roy; Wei, Ran; Sundue, Michael (Phytotaxa, 2024)
We conducted a molecular phylogenetic study of Athyrium focusing on species from Java, Bali, and Sulawesi using five chloroplast markers. We sample from type localities to help resolve the application of names which have been applied inconsistently throughout the Malesian floristic area and tropical Asia. We show that A. nigripes is known with certainty only from Indonesia and perhaps Malaysia, corroborating earlier conclusions that the name A. nigripes does not apply to plants from mainland China, or India. Moreover, we show that A. nigripes is closely related to A. pulcherrimum, a narrow endemic from Mt. Pangrango, Java. We also find a large polytomy of species including A. erythropodum from both Java and Taiwan, A. auriculatum, A. brevipinnulatum, and A. mearnsianum, that helps to both clarify species concepts and raises new questions about the application of names. Finally, we show that although the presence of spines and setae do not coincide with a recent infrageneric classification of Athyrium, these characters remain useful for distinguishing large species groups.